A Performance Evaluation Study for QoS-aware Web Services Composition Using Genetic Algorithms - Prado, Pedro F. do; Nakamura, Luis H. V.; Estrella, Julio C.; Santana, Marcos J.; Santana, Regina H. C. (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance), 2012)
In this paper four different Genetic Algorithms (GAs) are proposed to solve the QoS-aware Web Services Composition (QWSC) problem in six different search-space sizes and a realistic deadline (a point not covered in many related works). The results obtained are compared with some results from an Exhaustive Search (ES) algorithm that always guarantees the global optima. Differently from some related works, statistical techniques are adopted in this paper in order to ensure more precise results from the four GAs. The results obtained showed that the design of experiments and the performance evaluation can be used to determine which genetic operators are better suited for the QWSC problem.